2007
DOI: 10.1590/s0100-06832007000100017
|View full text |Cite
|
Sign up to set email alerts
|

Atributos químicos de um latossolo vermelho sob diferentes sistemas de preparo, adubações e plantas de cobertura

Abstract: RESUMOOs sistemas de preparo do solo e tipos de adubações levam à disposição diferenciada dos elementos minerais no perfil do solo, influenciando os seus atributos químicos. O objetivo deste trabalho foi verificar as alterações de alguns atributos químicos de um Latossolo Vermelho de cerrado, sob as adubações orgânica e mineral e plantas de cobertura, estabelecidas nos sistemas de semeadura direta e preparo convencional, sendo cultivado com feijão de inverno e algodão. O delineamento experimental utilizado foi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
1
27

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 6 publications
5
14
1
27
Order By: Relevance
“…These results corroborate those of Moreti et al (2007), who observed difference of 78.25 mg dm -3 between poultry manure dose and control. In the layer of 0.1-0.2 m, the contrast was significant with interaction of Dose x Management with soil chiseling for the poultry manure doses of 4.148 and 6.222 Mg ha -1 , and estimates of -7.07 and -8.67 mg dm -3 .…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…These results corroborate those of Moreti et al (2007), who observed difference of 78.25 mg dm -3 between poultry manure dose and control. In the layer of 0.1-0.2 m, the contrast was significant with interaction of Dose x Management with soil chiseling for the poultry manure doses of 4.148 and 6.222 Mg ha -1 , and estimates of -7.07 and -8.67 mg dm -3 .…”
Section: Resultssupporting
confidence: 92%
“…Similar results were obtained by Rós et al (2013), Scherer & Nesi (2009) and Andreola et al (2000), with the use of poultry manure. These results corroborate those of Moreti et al (2007), who observed that, in the layer of 0.0-0.1 m, Ca contents were higher when using poultry manure and poultry manure + half of the mineral fertilization, attributing it to the higher content of organic matter in the poultry manure, which promotes lower leaching of cations.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…For a sustainable agriculture, many management systems with mechanical fertilization can be studied aiming to maintain soil fertility (Moreti et al, 2007). The use of chisel plows in degraded pasture areas can break the compacted superficial layer of the soil and, in a certain way, incorporate poultry manure in the pasture, according to the recommendations of Brasil (2009).…”
Section: Introductionmentioning
confidence: 99%